Barriers and facilitators to following dietary recommendations for bone health: a qualitative study - Harleen Ghuttora; Lorena Kembel; Heidi Piovoso; Adrienne L Feasel; Julia MacLaren; April Matsuno; Tanis Fenton; Catherine B Chan; Gregory A Kline; Emma O Billington (BMC Nutrition)
Abstract Background An estimated one in two women and one in five men will experience a low-trauma fracture after age 50. Diet is an important mediator of bone health but individuals with or at risk of osteoporosis do not always meet recommended intake of specific nutrients (protein, calcium, vitamin D) and whole foods. We aimed to identify barriers and facilitating factors to following dietary recommendations for bone health among adults with or at risk of osteoporosis. Methods Adults aged ≥ 45 years who had been referred to a specialty osteoporosis clinic were recruited to participate in 4 virtual focus groups exploring barriers and facilitators to following dietary recommendations for bone health. Interest in a practical, bone-health focused Culinary Medicine program was also assessed. Results A total of 29 individuals were enrolled, 26 completed a pre-survey which asked about demographics and dietary habits, and 24 (age range 56–89 years, 21 female) attended one of four virtual focus groups. Principle barriers to following dietary recommendations for bone health highlighted by the focus group participants were: (1) living alone and cooking for one, (2) low motivation to prepare meals, and (3) dietary restrictions. Principal facilitators were: (1) preparing meals in advance, (2) online grocery shopping, and (3) engaging in exercise. Focus group participants expressed enthusiasm about participating in a Culinary Medicine program for bone health. Conclusion Our findings indicate that adults with or at risk of osteoporosis face multiple barriers to adhering with dietary recommendations. Bone-focused Culinary Medicine programming merits further study as a possible method of overcoming these barriers.